2019
DOI: 10.1016/j.jphotochem.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous photodegradation of Pyrimethanil and its commercial formulation with TiO2 immobilized on SiC foams

Abstract: Vine is one of the crops undergoing the most pesticide treatment. Due to the presence of pesticides residues in water and food, and the negative effects on human and wildlife health, it is necessary to develop an effective treatment. Photocatalytic oxidation using semiconductors is one of the advanced oxidation processes for degradation of organic pollutants in water and air. A TiO2 in nanopowder is an excellent photocatalyst that can mineralize a large range of organic pollutants such as pesticides and dyes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…cal) , and TiO 2 Sup.ac + cal was already expected, since the commercial P25 TiO 2 photocatalyst was used and it is a mixture of TiO 2 ‐A and TiO 2 ‐R whose mass fractions are in the range of 70% to 80% and 20% to 30%, respectively. In relation to anatase (A) and rutile (R) crystalline phases, the results corroborate with M'Bra et al and Souza et al who found 75% anatase and 25% rutile when using P25 TiO 2 in their work.…”
Section: Resultssupporting
confidence: 88%
“…cal) , and TiO 2 Sup.ac + cal was already expected, since the commercial P25 TiO 2 photocatalyst was used and it is a mixture of TiO 2 ‐A and TiO 2 ‐R whose mass fractions are in the range of 70% to 80% and 20% to 30%, respectively. In relation to anatase (A) and rutile (R) crystalline phases, the results corroborate with M'Bra et al and Souza et al who found 75% anatase and 25% rutile when using P25 TiO 2 in their work.…”
Section: Resultssupporting
confidence: 88%
“…TiO 2 /β-SiC foam material has proven its effectiveness for the removal of organic pollutants (Marien 2017;M'Bra et al 2019). Parameters which are commonly studied in photocatalytic process are pH, dye concentration, mass of catalyst, and effect of electron acceptors such as H 2 O 2 , KB r O 3 , K 2 SO 2 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the b-SiC foam surface is composed of a thin amorphous nanolayer exposing a high density of oxygenated surface groups, thereby favouring the anchorage of photocatalysts. [7][8][9]12 Binderless b-SiC alveolar foams have been already used as a TiO 2 support in water treatment. 7,[12][13][14] However, preparation of the foam-supported TiO 2 photocatalysts requires immobilizing or synthesizing TiO 2 onto the b-SiC support through a separate post-synthesis process, such that the TiO 2 /b-SiC foams can suffer detrimental stability problems that could provoke a release of the photocatalyst to water.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9]12 Binderless b-SiC alveolar foams have been already used as a TiO 2 support in water treatment. 7,[12][13][14] However, preparation of the foam-supported TiO 2 photocatalysts requires immobilizing or synthesizing TiO 2 onto the b-SiC support through a separate post-synthesis process, such that the TiO 2 /b-SiC foams can suffer detrimental stability problems that could provoke a release of the photocatalyst to water. The resistance of the catalyst-support interface towards the strains, derived from particle-to-particle and particle-uid mechanical interactions in the reactor environment, remains indeed an essential quality criteria for a good support, especially, in order to avoid the release of photocatalyst particles from the support.…”
Section: Introductionmentioning
confidence: 99%